Renovating the collected algorithms from ACM. - Hopkins, Tim (ACM transactions on mathematical software.)
Since 1960 the Association for Computing Machinery has published a series of refereed algorithm implementations known as the Collected Algorithms of the ACM (CALGO). Most of those published since 1975 are mathematical algorithms, and many of them remain useful today. In this paper we describe measures that have been taken to bring some 300 of these latter codes to an up-to-date and consistent state.